2016
DOI: 10.1037/edu0000085
|View full text |Cite
|
Sign up to set email alerts
|

Exploring reference group effects on teachers’ nominations of gifted students.

Abstract: Teachers are often asked to nominate students for enrichment programs for gifted children, and studies have repeatedly indicated that students' intelligence is related to their likelihood of being nominated as gifted. However, it is unknown whether class-average levels of intelligence influence teachers' nominations as suggested by theory-and corresponding empirical results-concerning reference group effects. Herein, it was hypothesized that when students' individual fluid and crystallized intelligence scores … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 95 publications
(144 reference statements)
3
49
0
Order By: Relevance
“…That is, in addition to the pretest measures of all dependent variables (academic achievement, interests, creativity, self-control, self-concept, social competence), we considered demographic variables, academic boredom, academic interests, intrinsic motivation, personality traits (assessed via parent ratings), school engagement, stressors, and mean class intelligence as covariates that were potentially important for the allocation procedure. We chose these variables because teachers were instructed to nominate children by considering a broad range of characteristics such as high (cognitive) abilities, creativity, interests, and motivation; we also used contextual factors such as mean class abilities (see Rothenbusch et al, 2016). It was important to include an extensive set of covariates to reduce bias in the treatment effect (see Thoemmes & Kim, 2011).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…That is, in addition to the pretest measures of all dependent variables (academic achievement, interests, creativity, self-control, self-concept, social competence), we considered demographic variables, academic boredom, academic interests, intrinsic motivation, personality traits (assessed via parent ratings), school engagement, stressors, and mean class intelligence as covariates that were potentially important for the allocation procedure. We chose these variables because teachers were instructed to nominate children by considering a broad range of characteristics such as high (cognitive) abilities, creativity, interests, and motivation; we also used contextual factors such as mean class abilities (see Rothenbusch et al, 2016). It was important to include an extensive set of covariates to reduce bias in the treatment effect (see Thoemmes & Kim, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Students can participate in the HCAP after being nominated as gifted by their teachers from their regular school. More precisely, teachers from any elementary school in Baden-W€ urttemberg can suggest students for participation by enrolling them in one academy (Rothenbusch, Zettler, Voss, L€ osch, & Trautwein, 2016). In line with more comprehensive conceptualizations of giftedness and to avoid nominations that are based on school achievement or intelligence only, teachers are instructed to nominate children for the whole program (and not a specific course) by considering a broad range of characteristics involving high (cognitive) abilities, creativity, interests, and motivation (Agreement, 2010).…”
Section: The Hector Children's Academy Programmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, research has shown that pupils' grade point averages (GPAs) are influenced by a frame-of-reference effect; that is, pupils in low average ability classes receive higher GPAs than equally able pupils in high average ability classes (Marsh, 1987;Trautwein et al, 2006). Similarly, a recent German study showed that, controlling for individual intelligence, the average intelligence level of a class had a negative effect on third graders' chances of being nominated by their teachers for enrichment programmes for gifted students (Rothenbusch et al, 2016). This strand of research thus suggests that teachers tend to judge pupils' ability relative to that of other pupils in the class.…”
Section: S Boone Et Almentioning
confidence: 99%